Analisis Manajemen Pemeliharaan Usaha Ternak Sapi Potong di Desa Pematang Sijonam Kecamatan Perbaungan - Matio Saurmauli Nainggolan; Nurul Khairunnisa Azhari; Natalia Kristina Sihombing; Ema Wijaya; Kiagus Muhammad Zain Basriwijaya (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
This study aims to analyzes the management of beef cattle maintenance in Pematang Sijonam Village, Perbaungan District, using a survey method through interviews and observations of farmers. Data includes maintenance techniques, feed quality, livestock health, and management practices that affect productivity. The results show that farmers are still using traditional techniques and facing obstacles in providing quality feed and managing livestock health. Factors such as farmer knowledge, skills, resource availability, and government support greatly affect the success of maintenance management. To increase the productivity and welfare of farmers, it is necessary to increase knowledge and skills through training, as well as government support in providing adequate resources and maintenance facilities.